O papel dos influenciadores de internacionalização no desempenho internacional das empresas de base tecnológica - Oliveira, Maria Carolina Serpa Fagundes de (2016)
Given the constant need for change, innovation generated by technology-based companies are able to make changes and efficient business models in increasingly insecure markets. At the same time, the context in which the technology industry of the country has gained more attention over the last decade by demonstrating how much domestic companies aim to develop this sector into a source of growth for Brazil. Therefore, this study aimed to analyze the role of internationalization influential on the international performance of technology-based companies (EBTs). For this purpose, an analysis was conducted, with a quantitative research which has been achieved by a survey execution, applied by the use of a questionnaire. Data collection was made by a 53 Brazilian EBTs located in innovation environments. Data were analyzed with univariate, bivariate and multivariate statistical techniques. The conceptual model of the research is based on two premises. For the internationalization influential analysis the Ribeiro et al. (2014) template has been used and for the international performance assessment the Gerschewski, Rose e Lindsay (2015) has been applied. With the results obtained, it was found that the internationalization influential linked directly to the company, concerning its internal and entrepreneur environment, are more relevant for the internationalization of EBTs than factors belonging to the external environment and which are not of total control of the companies. Therefore it was found that for the companies included in the sample, invest in international business is yet another result of their skills and management abilities than the benefits that the environment in which they operate can provide. On the other hand, regarding the role of those influencers on the international performance, it was found that while the external and internal factors generate a positive influence on the international performance, the factors related to the entrepreneur provide do not have an influence on such variable. By these means, it can be inferred that the determinants of such performance can be established by the following factors: (a) participate or have participated in some innovation habitats; (b) forming partnerships and strategic alliances for innovation; (c) making use of national government for internationalization; (d) develop innovation capabilities; (e) be geared to the international market; and (f) have international marketing skills.